A case for identifying smoking in presentations to the emergency department with suicidality. (April 2018) - Wilhelm, Kay; Handley, Tonelle; Reddy, Prasuna
Objectives: The aim of this study was to identify mental health and lifestyle factors predicting smoking among people at high risk of suicidal behaviour. Methods: Participants ( n = 363) completed self-report mental health and lifestyle measures at first appointment in a hospital clinic following presentation to the emergency department for deliberate self-harm or suicidal ideation. Results: The rate of daily smoking in this group, 61.4%, is more than four times the rate observed in the general population. Those with a history of previous deliberate self-harm were twice as likely to be smokers. Each one-point increase in poor health behaviours increased the odds of smoking by 22%. Conclusions: Identifying and managing smoking and related lifestyle behaviours are important considerations in routine clinical assessments.